2001
DOI: 10.1029/2000gl011773
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive decadal oscillations in the Arctic/Subarctic climate

Abstract: Abstract. A conceptual model of the Arctic climate system is generated by taking two key components in the coupled atmosphere-ice-ocean system, having a basis on a box model with water exchanges among the Arctic Basin, the Greenland

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The exact mechanism that causes Arctic warming is still unknown. However, it may be related to large‐scale atmospheric phenomena occurring on interannual scales like the North Atlantic Oscillation [ Dickson et al , 2000; Polyakov and Johnson , 2000] or Arctic Oscillation [ Thompson and Wallace , 1998; Ikeda et al , 2001].…”
Section: Discussionmentioning
confidence: 99%
“…The exact mechanism that causes Arctic warming is still unknown. However, it may be related to large‐scale atmospheric phenomena occurring on interannual scales like the North Atlantic Oscillation [ Dickson et al , 2000; Polyakov and Johnson , 2000] or Arctic Oscillation [ Thompson and Wallace , 1998; Ikeda et al , 2001].…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric circulation responses to the large surface heat loss in the BS have been proposed as one way to facilitate a positive feedback loop and thus maintain decadal oscillations in the Arctic air‐ice‐ocean system [ Ikeda ; Mysak and Venegas , ; Ikeda et al ., ; Bengtsson et al ., ]. We call this loop the “wind feedback.” In this feedback loop, the increased surface heat loss warms the lower atmosphere and leads to a local reduction in surface pressure (Figure d).…”
Section: Introduction and Focusmentioning
confidence: 99%
“…However, since observational data are scarce, this is mainly based on results from coupled ocean-atmosphere models (Delworth et al 1993(Delworth et al , 1997Jungclaus et al 2005). Ikeda et al (2001), Bengtsson et al (2004), and Goosse and Holland (2005) showed that increased heat transport into the Barents Sea affects the local interactions between atmosphere and ocean. The associated warming in the Barents Sea reduces the SLP that feed back positively on ocean circulation and heat transport.…”
Section: Introductionmentioning
confidence: 99%